Volatile versus Propofol General Anesthesia and Long-term Survival after Breast Cancer Surgery: A National Registry Retrospective Cohort Study. (27th June 2022) - Enlund, Mats; Berglund, Anders; Enlund, Anna; Bergkvist, Leif
Abstract : Background: Several retrospective studies using administrative or single-center data have failed to show any difference between general anesthesia using propofol versus inhaled volatiles on long-term survival after breast cancer surgery. Although randomized controlled trials are ongoing, validated data from national clinical registries may advance the reliability of existing knowledge. Methods: Data on breast cancer surgery performed under general anesthesia between 2013 and 2019 from the Swedish PeriOperative Registry and the National Quality Registry for Breast Cancer were record-linked. Overall survival was compared between patients receiving propofol and patients receiving inhaled volatile for anesthesia maintenance. Results: Of 18, 674 subjects, 13, 873 patients (74.3%) received propofol and 4, 801 (25.7%) received an inhaled volatile for general anesthesia maintenance. The two cohorts differed in most respects. Patients receiving inhaled volatile were older (67 yr vs. 65 yr), sicker (888 [19.0%] American Society of Anesthesiologists status 3 to 5 vs. 1, 742 [12.8%]), and the breast cancer to be more advanced. Median follow-up was 33 months (interquartile range, 19 to 48). In the full, unmatched cohort, there was a statistically significantly higher overall survival among patients receiving propofol (13, 489 of 13, 873 [97.2%]) versus inhaled volatile (4, 039 of 4, 801 [84.1%]; hazard ratio, 0.80; 95% CI, 0.70 to 0.90; P < 0.001). After 1:1 propensity score matching (4, 658 matched pairs), there was no statistically significant difference in overall survival (propofol 4, 284 of 4, 658 [92.0%]) versus inhaled volatile (4, 288 of 4, 658 [92.1%]; hazard ratio, 0.98; 95% CI, 0.85 to 1.13; P = 0.756). Conclusions: Among patients undergoing breast cancer surgery under general anesthesia, no association was observed between the choice of propofol or an inhaled volatile maintenance and overall survival. Abstract : Using data combining two national Swedish clinical registries from 2013 to 2019 for 18, 674 breast cancer surgery patients, the authors observed that 13, 873 (74.3%) received propofol general anesthesia and 4, 801 (25.7%) received inhaled volatile general anesthesia. In a propensity score–matched cohort of 9, 316 patients, there was no difference in overall survival between patients receiving propofol general anesthesia (4, 284 of 4, 658; 92.0%) versus inhaled volatile general anesthesia (4, 288 of 4, 658; 92.1%).